Student Engagement Online Pada Masa Pembelajaran Daring : Analisis Dimensi dan Faktor Demografi - Afriliani Dwi Hartati; Megawati Batubara (Jurnal Paedagogy, 2023)
This research aims to analyze the dimensions of online student engagement for students of the Faculty of Psychology, Padjadjaran University, during the online learning period and the demographic factors that influence it. The method used in this research was non-experimental with a quantitative approach. The research subjects were students of level one to level four of the Bachelor of Psychology Program at Padjadjaran University, totaling 94 people (level one = 26.6%, level two = 20.2%, level three = 25.5%, and level four = 27.7%), which was obtained using the method stratified random sampling. The instrument used was the Online Student Engagement Questionnaire (SEQ), totaling thirty-one items. The analysis technique used was descriptive analysis and t-test. The results of this study indicated that Psychology Undergraduate Program students had different levels of involvement in each online SEQ dimension. Students in this study showed high involvement in online engagement, active online learning, online teaching, online social interaction, online collaboration, and online contact with staff. However, they did not show involvement in the online academic relevance dimension. Moreover, the demographic factors affected student involvement in each online SEQ dimension in online learning, including class, gender, regional origin, learning facilities, study groups, and socioeconomic status.